Pola Rekreasi Anak Berkebutuhan Khusus (ABK) di Kota Bandung - Arief Rosyidie; Dini Adelina P; Yani Adriani (The Institute for Research and Community Services, Institut Teknologi Bandung, 2011)
Population of the Bandung city is considered as heterogen when based on demographic, economic, and social charateristics. Based on population condition, there is also a difable or disable group (ABK) who has special needs which must be met. One such requirement is the need for recreation. ABK have free time that can be used for recreation. There are factors that affect the recreational activities of difable children in Bandung. This paper discusses the recreation patterns of disable children based on their leisure or free time, with case study of disable children in primary education level of Bandung city. Interviews were conducted to the respondents of disable children (ABK), their parent/guardian teacher. The result of study showed that the disable children (ABK) have a lot of free time which was mostly used for recreation, but only a small percentage of respondents had an opportunity to have recreation outside. The role of stakeholders, especially city government, should be improved to give greater attention to the disable children, including opportunities for recreation.Keywords: recreation, disable children, leisure, Bandung city